Mapping Brain Spatial Metabolic Atlas Reveals Anesthesia-Induced Region-Specific Alterations - Wei Feng; Lijuan Pang; Chun-Jie Liu; Jiuming He; Lisi Wang; Zhenyu Xu; Yinglong Zeng; Zengqiang Yuan; Chao Zhang (Neuroscience Bulletin, 2026)
The brain supports consciousness through regional heterogeneity. However, the spatial complexity of its metabolome under anesthesia remains unclear. In this study, we established a spatial metabolomic atlas of the mouse brain under wakefulness, inhalation anesthesia, and injectable anesthesia. In total, 727 metabolites were identified and spatially mapped across 11 representative brain regions. We found that anesthesia significantly altered the brain metabolic landscape in a spatially dependent manner, particularly affecting lipid metabolism, amino acid pathways, and neurotransmitter-related metabolites. Furthermore, we monitored the cortical microvascular blood flow and blood oxygen levels during anesthesia. We observed that different anesthesia modalities induced distinct changes in cortical arteriovenous microvascular hemodynamics, suggesting a potential association between metabolic alterations and cerebrovascular regulation. We developed an open-access online database, the mouse brain spatial metabolome atlas ( https://mbsma.liulab.cloud/#/dashboard ), to facilitate access to and analysis of the dataset. Our study reveals anesthesia-induced spatial metabolic reprogramming in the brain, providing insights into neural metabolism and cerebrovascular dynamics, with implications for perioperative brain protection and safer anesthesia strategies.